New perspective in cell communication: potential role of ultra-weak photon emission - Prasad, Ankush; Rossi, Claudio; Lamponi, Stefania; Pospíšil, Pavel; Foletti, Alberto (Journal of photochemistry and photobiology. B, Biology, 2014)
Evolution has permitted a wide range of medium for communication between two living organism varying from information transfer via chemical, direct contact or through specialized receptors. Past decades have evidenced the existence of cell-to-cell communication in living system. Several studies have demonstrated the existence of one cell system influencing the other cells by means of electromagnetic radiations investigated by the stimulation of cell division, neutrophils activation, respiratory burst induction and alteration in the developmental stages, etc. The responses were evaluated by methods such as chemiluminescence, ultra-weak photon emission, generation of free oxygen radicals, and level of thiobarbituric acid-reactive substances (TBARS). The cellular communication is hypothesized to occur via several physical phenomenon's, however the current review attempts to provide thorough information and a detailed overview of experimental results on the cell-to-cell communication observed in different living system via ultra-weak photon emission to bring a better understanding and new perspective to the phenomenon.
Keywords: biochemie; Animals; Cell Communication; Humans; Photobiology; lidé; zvířata; fotony; Photons; mezibuněčná komunikace; fotobiologie; Biochemistry